Simple methodology for methylmercury and inorganic mercury determinations by high-performance liquid chromatography-cold vapour atomic fluorescence spectrometry - Ramalhosa, Elsa (2001)
An analytical methodology was developed to separate and quantify methylmercury (MeHg) and inorganic mercury by high-performance liquid chromatography (HPLC)-cold vapour atomic fluorescence spectrometry (CV-AFS). The use of UV oxidation of the organic forms of mercury, the tin(II) chloride reduction in acidic medium of mercury and the introduction of a water vapour trap based on H2SO4/CaCl2 resulted in a low detection limit (DL) (10 +/- 2 pg, mean value +/- S.D.). The apparatus was operationally optimised through the modified simplex method leading to an increase of the signal by a factor of 2. The method performance has been tested by determining the MeHg concentration in a sediment certified reference material (CRM) and the results were statistically indistinguishable from the certificate value (alpha = 0.05) both for the mean value and S.D.